POSITIVE POLITENESS STRATEGIES ON CATWOMAN MOVIE - Yuniarti, Eka; Natsir, M.; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
Based on the importance of positive politeness in communication, the researcher intended to analyze how positive politeness strategy uttered by Patience Phillips on Catwoman Movie. It is conducted to find out the kinds and purpose of positive politeness strategy employed by Patience Phillips and also to investigate the factors influencing Patience Phillips applying those strategies in relation to Brown and Levinson’s theory of politeness strategy. This research deals with pragmatics approach. There are two factors influencing Patience Phillips in applying positive politeness strategy. Namely payoff and circumstances, the payoff factors and the circumstances factors (including relative power, social distance, and size of imposition) influence Patience Phillips in several data. Finally, the researcher expects this research will be useful for future researcher who conducted for the same field. It is suggested to further researchers to be able to investigate other objects and may try to analyze from different focus, such as focused on negative politeness, bald on record or off record strategy or used another principal theory of politeness such as politeness theory from Leech, Grice, Scollon or Lakoff.